CULTURE SHOCK EXPERIENCED BY DRE PARKER IN KARATE KID MOVIE - Rachmawati, Teriana Nur; Margono, Yosep Bambang (Universitas 17 Agustus 1945 Semarang, 2024)
Living in an area or moving just for a vacation to another place makes a person feel stressed and confused if they don't know how to face and overcome when they can't adapt. It's called culture shock. Culture shock is the feeling of disorientation experienced by someone who is suddenly confronted with an unfamiliar culture, way of life, or attitude. It can happen when someone who lives in another place has a different culture. This research is based on a film entitled Culture Shock Experienced by Dre Parker where Dre Parker as the main character experiences this culture shock. This study also refers to Oberg who stated the aspects, factors, and phases experienced by Dre. This research was conducted using qualitative methods with observation and documentation to see the film, hear the voice or dialogue and search for scripts related to this film on the internet. The results of the study show that culture shock is not so bad to experience, as long as a person is able to survive and adapt well and correctly in his new environment or culture. Key words: Culture, culture shock, experienced